Pathogenic tau induces an adaptive elevation in mRNA translation rate at early stages of disease. - Zuniga, G.; Katsumura, S.; De Mange, J.; Ramirez, P.; Atrian, F.; Morita, M.; Frost, B. (Aging Cell, 2024)
Alterations in the rate and accuracy of messenger RNA (mRNA) translation are associated with aging and several neurodegenerative disorders, including Alzheimer's disease and related tauopathies. We previously reported that error-containing RNA that are normally cleared via nonsense-mediated mRNA decay (NMD), a key RNA surveillance mechanism, are translated in the adult brain of a Drosophila model of tauopathy. In the current study, we find that newly-synthesized peptides and translation machinery accumulate within nuclear envelope invaginations that occur as a consequence of tau pathology, and that the rate of mRNA translation is globally elevated in early stages of disease in adult brains of Drosophila models of tauopathy. Polysome profiling from adult heads of tau transgenic Drosophila reveals the preferential translation of specific mRNA that have been previously linked to neurodegeneration. Unexpectedly, we find that panneuronal elevation of NMD further elevates the global translation rate in tau transgenic Drosophila, as does treatment with rapamycin. As NMD activation and rapamycin both suppress tau-induced neurodegeneration, their shared effect on translation suggests that elevated rates of mRNA translation are an early adaptive mechanism to limit neurodegeneration. Our work provides compelling evidence that tau-induced deficits in NMD reshape the tau translatome by increasing translation of RNA that are normally repressed in healthy cells.